EVALUASI PROGRAM RELOKASI PEDAGANG KAKI LIMA DALAM RANGKA REVITALISASI BANJIR KANAL BARAT (BKB ) KOTA SEMARANG - Muhammad Taufik Kurniawan; Priyatno Harsasto; Puji Astuti (Journal of Politic and Government Studies, 2016)
Abstrack             Vendors is one of the people's livelihood Semarang. By looking at the socio-economic problems in urban communities, do not be surprised if the established competition of human resources to compete for jobs. consequently many urban communities that have a lower HR chose work as street vendors. Many of them trade by occupying land that is not its designation as a land trade, as a result of the dirty slum areas as well as traffic stalled because their shanties there who occupy basudewo shoulder of the road adjacent to BKB. With the parent program is normalization BKB Semarang, the street vendors have to be moved. However, after the program was realized, a new problem arises in part because the street vendors that have been provided by the city of Semarang does not correspond to their expectations and of the visitors or the public so that the merchandise was not sold and no income and caused unemployment. Thus this study aims to determine the level of success of the program.             The purpose of this study was to identify the level of success of the relocation program PKL West Flood Canal . This study is a qualitative research method , the type of research used in this research is descriptive . Data taken from interviews, documentation and data from official documents Semarang city market .             By looking at the studies in the field and interviews , the success rate of the program can actually be said to be 70 % successful and the rest of emotion uncorrected used as the sustainability of this program which is still a question mark for a program should be made in order to alleviate a problem instead of a new problem . The second thing is the Semarang city government as a hands-off with the fact that the program is poorly managed and not try to find another alternative to solve the problems .             Enabling and inhibiting factors relocation process is Trader This trader is given continuously socialization and persuaded to be relocated by the city of Semarang and Central Java provincial government . Second , the merchants do not refuse to be relocated . Some solutions ditwarkan is providing another place that could be used as a place to sell , deliver events continuously by taking a location near the location of the relocated street vendors in order to bring in customers or the public . Keywords : Empowerment Kokrosono And Waru Street vendors